The relationship of obstructive sleep apnea and cardiovascular diseases from the perspective of evidence-based medicine. Part 2 - M. V. Agaltsov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
The results of prospective studies, meta-analyzes and systematic reviews on the associations of obstructive sleep apnea (OSA) with various cardiovascular diseases (CVD) were analyzed. The second part is devoted to the analysis of the relationship between OSA and CVD such as coronary artery disease, cerebrovascular disease, heart failure, pulmonary hypertension. All of them are associated with breathing-related sleep disorders. Among these diseases, the most significant associations were revealed for OSA and heart failure, OSA and cerebrovascular disease. Separately, the relationship of OSA with cardiovascular mortality is discussed. Most observational studies have shown that OSA without treatment increases mortality rate.